Women’s empowerment as a protective factor against intimate partner violence in Bangladesh: a qualitative exploration of the process and limitations of its influence - Schuler, Sidney Ruth; Lenzi, Rachel; Badal, Shamsul Huda; Bates, Lisa Michelle (© 2016 SAGE Publications Inc., 2018)
This article was published in the Violence Against Women [© 2016 The Author(s) ] and the definite version is available at: https://doi.org/10.1177/1077801216654576 The Article's website is at: http://journals.sagepub.com/doi/10.1177/1077801216654576